ENT 530 Business Model Canvas: ScrunchieKit / Nurul Syafizah Mohd Ali ... [et al.] - Mohd Ali, Nurul Syafizah; Mohamad Husni, Marsha Alya; Khasnan, Nurul Izzah; Zainudin, Mohamad Sharol; Syed Hassan, Syarifah Nabilah (2021)
This report will explain about the Business Model Canvas (BMC) for SrunchieKit. SrunchieKit is actually a hairband made from silk but has other uses as well such as to be a bracelet and also a mask. This is a new innovation for Scrunchies that is usually just for hairband. Since we all are in pandemic COVID-19 phases, the mask is important to be worn anywhere. Our premise is located at a famous and busy city in Selangor which is at Section 7 Shah Alam and planning to open on 1st July 2021. The uniqueness of the material that has been used to produce the scrunchies and also the strategic location for the premise easily accessible to potential customers. Besides, the SrunchieKit’s SWOT analysis can be determined by looking at the competitors, which are Scrungie and Theuploft. These two competitors have become the benchmark for SrunchieKit in order to have better planning in handling business efficiently and successfully. As the major BMC purpose is to assist new businesses in planning business accurately to ensure there are no any major problems if the company operates the business in the future. SrunchieKit has followed the BMC guidelines to determine if their business prospects are worthwhile if they choose to proceed. It includes customer segment, value propositions, channels, customer relationships, revenue streams, key activities, key resources, key partnership, and cost structure. The further explanation about the BMC of SrunchieKit may be found in this report.